IMPLEMENTASI PEMBELAJARAN STORYTELLING GUNA MENINGKATKAN LANGUAGE SKILL PADA ANAK USIA DINI DI TAMAN KANAK-KANAK (TK) PKK PELITA BANGSA PAKUNIRAN PROBOLINGGO - Jazilurrahman Jazilurrahman; Halimatus Sa’diyah; Zaenol Fajri (Raudhah - Proud To Be Professional, 2023)
Children are a mandate from Allah SWT (God Almighty) who must be educated, nurtured and cared for carefully so that later they become perfect human beings, useful for religion, nation and state. With education, children are expected to be able to develop all their potential. Education must also be able to give birth to quality students, both physically and mentally in order to achieve the expected goals. Early childhood education (PAUD) in general is education that is organized with the aim of facilitating the growth and development of children as a whole. Early childhood education also emphasizes all aspects of the child's intelligence and personality. This education is given to children aged 4-6 years, especially Kindergarten (TK) or other similar education within that age range. Kindergarten is a form of formal pre-school education that helps the physical and spiritual growth and development of children before entering elementary school education. The purpose of this study was to determine children's language skills by using storytelling learning at PKK Pelita Bangsa Pakuniran Kindergarten. The research method uses a type of qualitative research and a case study approach. The research subjects were in class A with a total of 25 children, there were 12 boys and 13 girls. The data collection technique was using snakeball sampling, the data sources used were primary and secondary. Data collection techniques through interviews, observation and documentation. Data analysis uses Miles Huberman analysis which consists of data reduction, data display and drawing conclusions. The results of the study showed that this storytelling media can facilitate learning and can improve children's language development. In addition to the fun of this storytelling media, there are picture story books and hand puppets where children really like illustrated stories and hand puppets so that children become enthusiastic about learning. This storytelling media can also improve children's way of thinking, add new vocabulary, add to children's language and also children's curiosity to learn new things and this storytelling media can also make it easier for teachers to convey learning to children.